Cannabis Use and Affective Processing: a Brain Structure Analysis - (:unkn) unknown (My University, 2016)
Cannabis is the most commonly used illicit drug amongst adolescents and young adults in the United States. Previously, cannabis and its components have been associated with differences in affective processing and neural functioning. Participants (ages 16-25) were cannabis users and non-users excluded for psychiatric disorders, major medical conditions, and excessive other drug use. A series of multiple regressions examined whether past year cannabis use and cannabis x gender predicted measures of emotional face processing (using the PennCNP affective battery) as well as volumes in bilateral prefrontal, temporal, limbic, and cerebellar regions, as well as frontolimbic white matter tracts. Subsequently, Pearson correlations were conducted within the cannabis group to assess whether brain regions significantly associated with cannabis use predicted mood and affective processing. Increased cannabis use was associated with higher Acuity Neutral scores, smaller left rostral anterior cingulate (rACC) volumes, larger superior temporal volumes, and reduced right uncinate fasciculus mean diffusivity. Significant cannabis x gender interactions were observed for left rACC and forceps minor fractional anisotropy (FA). Greater cannabis use was associated with smaller left rACC volumes only within females, as well as greater forceps minor FA in females and reduced FA in males. Within the cannabis-using group, smaller rACC volumes were correlated with lower Emotion Discrimination Correct scores. These findings suggest that cannabis use exerts dose dependent effects on frontolimbic circuitry, which are in turn associated with deficits in affective processing. This may be one potential mechanism underlying high comorbidity rates between chronic cannabis use and psychiatric disorders.
Keywords: Affect; Cannabis; DTI; Frontolimbic; Marijuana; MRI